Pro WPF in C♯ 2008 : Windows presentation foundation with .NET 3.5 - MacDonald, Matthew (Springer, 2017)
The Microsoft Windows Presentation Foundation provides the foundation for building applications and high–quality user experiences in Windows Vista. WPF blends application user interface, documents, and media content to provide richer control, design, and development of the visual aspects of Windows programs.